Effects of the Temperature-Time Regime of Curing of Composite Patch on Repair Process Efficiency - Kondratiev, Andrii; Píštěk, Václav; Smovziuk, Lina; Shevtsova, Maryna; Fomina, Anna; Kučera, Pavel; Prokop, Aleš (Polymers, 2021)
Repair procedures with the use of composite patches are considered to be the most effective among the current technologies of repair of the structures of various applications. In the process of moulding-on of a patch made of polymeric composite material by means of curing, technological stresses arise in the patch. Determination of residual technological stresses is a priority task for the modelling of the repair process. Reduction of residual stresses can be achieved by optimization of the mode of repair patch curing. For meeting this objective, the method for determination of technological stresses, which arise in the structure under repair in the process of curing of a composite patch, has been developed. The method takes into account the shrinkage, change in physico-mechanical characteristics, rheological processes occurring in the binder during moulding process, and determination of stresses in the structure under repair at any time. Therefore, premature failure of the repair joint at the stage of repair can be avoided. It is shown that the method adequately describes the level of deformations and stresses in the structure being repaired at the stage of heating and holding of the composite patch. Increase in the moulding temperature leads to a reduction in residual stresses in the structure under repair. However, current stresses at the stages of heating and temperature holding are increased significantly. Reliability of assumptions and developed method is confirmed by the comparison with the experimental data. The obtained experimental graph of total deformation of the composite patch allowed us to clearly determine the moment of residual stress occurrence in the structure under repair. This moment matches quite exactly (with the discrepancy not exceeding 5 min) the gel point determined analytically based on dependence of the degree of curing on the moulding mode. Consequently, the research together with the results previously obtained allows making an integrated choice of geometric parameters of the repair composite patch and temperature-time regime of its curing in order to ensure the specified level of strength and stiffness of the structure under repair.
Keywords: binder shrinkage; gelation; temperature–time regime